2012
DOI: 10.5402/2012/621518
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Physicochemical Characterization of Some Oils as Potential Feedstock for Biodiesel Production

Abstract: Physicochemical properties ofCucurbita pepo, Brachystegia eurycoma, Cucumis melo, Luffa cylindrica, andArachis hypogaeaoils were studied to determine their potential as viable feedstock for biodiesel production. The nonedible oils were extracted by solvent extraction using n-hexane while the oil ofArachis hypogaeawas procured. All the oils were characterized for specific gravity, pH, ash content, iodine value, acid value, saponification value, peroxide value, free fatty acid, flash point, kinematic viscosity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
51
3
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 14 publications
9
51
3
2
Order By: Relevance
“…It has been reported that the amount of potassium hydroxide, KOH, that requires neutralizing the fatty acid contained in CKO is 1 mg of FAME [17][18][19]. According to Azhari et al [19], high amount of soap would be produced simultaneously when transesterification reaction of the feedstock contains a high amount of FFA than the required maximum amount of basic homogenous catalyst.…”
Section: Measurement Of Free Fatty Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the amount of potassium hydroxide, KOH, that requires neutralizing the fatty acid contained in CKO is 1 mg of FAME [17][18][19]. According to Azhari et al [19], high amount of soap would be produced simultaneously when transesterification reaction of the feedstock contains a high amount of FFA than the required maximum amount of basic homogenous catalyst.…”
Section: Measurement Of Free Fatty Acidmentioning
confidence: 99%
“…Hexane has been continuously refluxed until the colour of the hexane in the thimble is very clear. This process requires a longer period of time and only few amounts of oil recovered as compared to other technique [17,18]. The extracted CKO has been filtered and heated to eliminate solid impurities.…”
Section: Extraction Of Crude Karanjamentioning
confidence: 99%
“…Dils are classified as drying, semi drying and non-drying on the basis of iodine value. Dils with an iodine value above 125 g I2 /100 g are classified as drying oils; those with iodine value between 110 and 140 g I2 /100 g are classified as semidrying oils and those with iodine value less than 110 g I2 /100 g are considered as nondrying oils (Ibeto et al, 2012). The characterized fish oils through different process were semidrying oils except hydrolyzed oil which was nondrying oil.…”
Section: Physical-chemical Characterizationmentioning
confidence: 99%
“…However, availability of these raw materials varies. This necessitates the search for new low-cost agricultural crops (Ibeto et al, 2012;Atabani et al, 2013c). Globally, there are more than 350 oil-bearing crops identified for biodiesel production (Atabani et al, 2012).…”
Section: Introductionmentioning
confidence: 99%